Pesantren for elderly: Study of the spiritual empowerment of elderly women in Pondok Sepuh Payaman, Magelang - Dwi Agustina (SIMULACRA: JURNAL SOSIOLOGI, 2020)
This study aims to determine the spiritual empowerment in Sepuh Payaman Cottage, Magelang. Spiritual empowerment is an effort to reduce the anxiety of the elderly about death. In old age humans are often associated with death that is getting closer. Preparing elderly mental health in the face of death is a basic requirement for the community in addition to physical and social health. In this study used a qualitative method approve case study, with the process of collecting data using interviews and observations. In order to analyze the data we used the disengagement theory of social gerontology. The findings in this study that spiritual empowerment was carried out within 24 hours and framed through ritual and social worship. The teaching pattern is emphasized in lecture-listening and learning by doing. The motivation of the elderly and family support is a driving factor for the elderly, while the decline in physical function is a limiting factor. In the pattern of spiritual empowerment, implications are found including, 1) Obtaining inner peace; 2) Getting closer to God; 3) Increasing the faith of the elderly; 4) Able to read Al-Qur’an; 5) Growing humanity; and 6) Establishment of new relations. The findings of this study can be used as an alternative and answer to reduce the level of anxiety in the elderly related to death.